Only One Place of Redress : African Americans, Labor Regulations, and the Courts from Reconstruction to the New Deal - Bernstein, David E. (Book collections on Project MUSE., 2001)
Focuses on the role facially-neutral labor regulations played in institutionalizing discrimination against African Americans in the period between Reconstruction and the civil rights era.